Co-cultivation of Lactobacillus acidophilus and Bacillus subtilis mediates the gut-muscle axis affecting pork quality and flavor - Zhixin Lin; Xinchen Zhou; Tingting Lu; Wendong An; Shenghao Chen; Suchen Li; Hui Miao; Xinyan Han (Journal of Animal Science and Biotechnology)
Abstract Background Pork quality and flavor are critical determinants of consumer preference, yet the role of gut microbiota in shaping meat characteristics remains underexplored. In this study, we investigated how a probiotic consortium (FAM: Lactobacillus acidophilus and Bacillus subtilis) modulates the gut-muscle axis to enhance pork flavor. Results In finishing pigs, FAM supplementation significantly increased flavor-associated nucleotides and umami-enhancing amino acids in longissimus dorsi muscle. Metagenomic analysis revealed FAM-driven enrichment of glycan-degrading Prevotella and short-chain fatty acid-producing Phascolarctobacterium, accompanied by reduced antibiotic resistance genes and virulence factors. Spearman correlation linked Prevotella copri abundance with elevated muscle amino acids, suggesting microbial-encoded CAZymes as key mediators. Conclusions This study provides the first evidence that probiotic-induced gut microbiota remodeling enhances pork flavor through metabolic cross-talk along the gut-muscle axis. The findings suggest a novel strategy for improving pork quality via dietary interventions targeting gut microbiota.